2021
DOI: 10.3390/nano11061627
|View full text |Cite
|
Sign up to set email alerts
|

Hollow Silica Particles: A Novel Strategy for Cost Reduction

Abstract: Thermal insulation materials are highly sought after for applications such as building envelopes, refrigerators, cryogenic fuel storage chambers, and water supply piping. However, current insulation materials either do not provide sufficient insulation or are costly. A new class of insulation materials, hollow silica particles, has attracted tremendous attention due to its potential to provide a very high degree of thermal insulation. However, current synthesis strategies provide hollow silica particles at ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…The charge density of silica increases with the pH increase. Hence, the rapid formation of hollow particles is attained [136] …”
Section: Research Trends On Porous Scaffoldsmentioning
confidence: 99%
See 2 more Smart Citations
“…The charge density of silica increases with the pH increase. Hence, the rapid formation of hollow particles is attained [136] …”
Section: Research Trends On Porous Scaffoldsmentioning
confidence: 99%
“…Adapted from Bao et al [135] with permission from Elsevier. [135] with permission from Elsevier, and from Spence et al [136] with permission from MDPI.…”
Section: Techniques For Infiltration Of Hydrides Into Shns Scaffold A...mentioning
confidence: 99%
See 1 more Smart Citation
“…HSPs with an average diameter of 300 nm were synthesized by using a previously reported method (details ESI †). 30,32 CFs (diameter: 50-100 nm; 3% solid content, from University of Maine Process Development Center) were mixed in water (4 mg mL À1 ) by homogenizing with a homogenizer (IKA-T18 digital Ultra Turrax) at 15 000 rpm for 8 h before mixing with HSPs. HSPs and a CF-based composite was prepared by mixing 80 wt% HSPs with 19.5 wt% CF in water.…”
Section: Composite Fabricationmentioning
confidence: 99%
“…[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] We recently demonstrated that HSPs can be synthesized very inexpensively by recycling the solvents. 32 HSPs can provide very high thermal insulation at a lower cost; however, because HSPs are a powder that is usually in the nano-micrometer size range, they are a health hazard, difficult to handle and transport, and can be messy to use. 1,33,34 For example, it is difficult to ll HSPs in a wall.…”
Section: Introductionmentioning
confidence: 99%